Moralization and Decriminalization of Consensual Adultery Punishment from the Perspective of Islamic Criminal Law and the New Criminal Code - Haniyah, Haniyah; Handayani, Budi; Samawati, Wiati (Faculty of Shariah UIN Ponorogo, 2025)
The reformulation of morality-based criminal offenses in the New Indonesian Criminal Code (KUHP), particularly regarding the criminalization of consensual adultery, raises questions about the limits of state intervention in the private sphere of citizens. In contrast, Islamic criminal law considers adultery (zina) as a jarimah with strong normative and theological foundations, accompanied by strict evidentiary requirements. This study compares the criminalization of adultery in the New KUHP, particularly Articles 411 and 412, with Islamic criminal law, while examining the influence of legal politics and moral value sources on both systems. The research employs a normative legal methodology with conceptual, statutory, and comparative approaches, and analyzes primary and secondary data qualitatively through systematic and contextual reading. The findings show that the New KUHP emphasizes social morality through a complaint-based offense mechanism, limiting state intervention in private matters, while still upholding moral norms. Islamic criminal law, on the other hand, treats adultery as a violation of divine and social order, but its strict evidentiary mechanisms and the principle of dar’ al-ḥudūd bi al-shubuhāt prevent arbitrary criminalization and protect individual rights. These findings highlight the importance of balancing collective moral values, respect for private space, and legal certainty in shaping criminal policy. This study is expected to serve as a reference for national criminal law reform and to broaden cross-system understanding of the relationship between morality, individual rights, and criminalization policy.